Gray Matter Nucleus Hyperintensity After Monthly Triple-Dose Gadopentetate Dimeglumine With Long-term Magnetic Resonance Imaging. Issue 10 (October 2020) - DeBevits, John J.; Munbodh, Reshma; Bageac, Devin; Wu, Rong; DiCamillo, Paul A.; Hu, Chaoran; Wang, Lihong; Naismith, Robert T.; Karimeddini, David; Dhib-Jalbut, Suhayl; Redko, Sviatoslav; Cook, Stuart D.; et al.
Abstract : Objectives: Gadolinium deposition is widely believed to occur, but questions regarding accumulation pattern and permanence remain. We conducted a retrospective study of intracranial signal changes on monthly triple-dose contrast-enhanced magnetic resonance imaging (MRI) examinations from the previously published Betaseron vs. Copaxone in Multiple Sclerosis With Triple-Dose Gadolinium and 3-Tesla MRI Endpoints Trial (N = 67) to characterize the dynamics of gadolinium deposition in several deep brain nuclei and track persistence versus washout of gadolinium deposition on long-term follow-up (LTFU) examinations (N = 28) obtained approximately 10 years after enrollment in the Betaseron vs. Copaxone in Multiple Sclerosis With Triple-Dose Gadolinium and 3-Tesla MRI Endpoints Trial. Materials and Methods: Using T2 and proton density images and using image analysis software (ITK-SNAP), manual regions of interest were created ascribing boundaries of the caudate nucleus, dentate nucleus, globus pallidus, pulvinar, putamen, white matter, and air. Intensity analysis was conducted on T1-weighted fat-saturated (fat-sat) images using the FSL package. A linear rigid-body transform was calculated from the fat-sat image at each target time point to the region of interest segmentation reference time point fat-sat image. Serial MRI signal was analyzed using linear mixed regression modeling with random intercept. Annual MRI signal changes including LTFU scans were assessed with t test. Results: During monthly scanning, all gray matter structures demonstrated a significant ( P < 0.0001) increase in contrast-to-noise ratio. Yearly changes in deposition showed distinctive patterns for the specific nucleus: globus pallidus showed complete retention, pulvinar showed partial washout, while dentate, caudate, and putamen returned to baseline (ie, complete washout). Conclusions: Monthly increased contrast-to-noise ratio in gray matter nuclei is consistent with gadolinium deposition over time. The study also suggests that some deep gray matter nuclei permanently retain gadolinium, whereas others demonstrate washout of soluble gadolinium. Abstract : Supplemental digital content is available in the text.